Interactions between gut microbiota, plasma metabolome and brain function in the setting of a HIV cure trial - Borgognone, Alessandra; Prats, Anna; Sharma, Ashish Arunkumar; Martinez-Zalacaín, Ignacio; Soriano-Mas, Carles; Brander, Christian; Clotet, Bonaventura; Moltó, José; Mothe, Beatriz; Sekaly, Rafick-Pierre; Paredes, Roger; Muñoz-Moreno, Jose A. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe intestinal microbiota composition has been linked to neurocognitive impairment in people with HIV (PWH). However, the potential interplay of microbial species and related metabolites, particularly in the context of an HIV cure strategy remains underexplored. The BCN02 trial evaluated the impact of romidepsin (RMD), used as a HIV-1 latency reversing agent and with reported beneficial neurological effects, combined with the MVA.HIVconsv vaccine on virus control during 32-weeks of monitored antiretroviral treatment interruption (MAP) in early-treated HIV-infected individuals. Here, we analyzed longitudinal gut microbiome, plasma metabolome and brain functioning data to identify potential associations and novel putative biomarkers of HIV-associated neurocognitive disorders (HAND).MethodsData from fecal shotgun metagenomics, plasma metabolome, cognitive (standardized neuropsychological test score covering 6 cognitive domains, NPZ-6), functional (neuropsychiatric symptoms) and neuroimaging assessments were obtained and evaluated in 18 participants before and after RMD administration, and at the study end (post-MAP follow-up) in the BCN02 trial.ResultsParticipants with neurocognitive impairment (Lower vs. Higher NPZ-6 score group) were enriched in bacterial species, including Desulfovibrio desulfuricans, Sutterella wadsworthensis and Streptococcus thermophilus, and showed higher 1,2-propanediol degradation microbial pathway levels, before RMD administration. A multi-omics profiling showed significant and positive correlations between these microbial features and lipid-related metabolic pathways, previously linked to neurological disorders (i.e., sphingolipid, ether lipid, and glycerophospholipid metabolism), in participants with neurocognitive impairment, before RMD administration. Three indices (microbial-, metabolite-based and combined) obtained from the discriminant features were assessed longitudinally, showing progressive similarities between NPZ-6 score groups over time. Furthermore, the three indices and related discriminant features correlated negatively with functional outcomes, such as quality of life and daily functioning, and positively with depression, stress and CNS-related symptoms before RMD administration, while these associations became less discernible at the subsequent timepoints.ConclusionsWhile the direct effect of the intervention on the observed shifts cannot be conclusively determined in this study settings, these findings strengthen the link between gut bacteria, related metabolites, and neurocognitive function in PWH, and provide an analytical framework for future validation studies aimed at discovering predictive biomarkers for neurocognitive impairment in PWH.